THE RELATIONSHIP AMONG LEARNING DISCIPLINE, LEARNING INTERACTION WITH PEERS AND PARENT'S ATTENTION WITH LEARNING ACHIEVEMENT OF MATHEMATICS - Muhammad Raezia; Aris Thobirin (Universitas Ahmad Dahlan, 2019)
This research is motivated by VII students of SMP Negeri 9 Yogyakarta. They are less disciplined in learning, lack learning interaction with peers, and lack parental attention. This study aims to determine whether or not a positive and significant relationship among learning discipline, learning interaction with peers, and parents' attention with learning achievement of mathematics students class VIII State Junior High School (SMP Negeri) 9 Yogyakarta in odd semester academic year 2017/2018. This research population comprises all students in grade VIII of SMP Negeri 9 Yogyakarta in the odd semester academic year 2017/2018, consisting of grades VIIIA, VIIIB, VIIIC, VIIID, and VIIIE VIIIF, totaling 203 students. Sampling technique using random sampling technique and class VIII D is chosen as the sample class. The instrument of collecting data using a learning discipline questionnaire, a learning interaction questionnaire with peers, and the parent's attention and mathematics test questionnaire. The analysis prerequisite test includes a normality test, linearity tests, and independent tests. Data analysis to hypotheses testing using correlation analysis product-moment and double linear regression analysis. This research shows that if there is positive and significant learning discipline, learning interaction with peers and parents' attention with learning achievement of mathematics students class VIII SMP Negeri 9 Yogyakarta in the odd semester academic year 2017/2018. This is indicated by Fcount = 5,29268 and Ftable = 2,92228, Fcount > Ftable with R = 0,5883 and R2 = 0,3460 with Big relative contribution and effective contribution